Effects of peripheral electromagnetic stimulation after an eccentric exercise-induced delayed-onset muscle soreness protocol in professional soccer players: a randomized controlled trial - Hugo Keriven; Alberto Sánchez-Sierra; Alberto Sánchez-Sierra; Alberto Sánchez-Sierra; Diego Miñambres-Martín; Ángel González de la Flor; Guillermo García-Pérez-de-Sevilla; Diego Domínguez-Balmaseda; Diego Domínguez-Balmaseda (Frontiers in Physiology, 2023)
Introduction: To examine the effects of peripheral electromagnetic stimulation in male professional soccer players on markers of Delayed Onset Muscular Soreness (DOMS), induced by a protocol of exercise (60 min of eccentric and plyometric).Methods: A randomized controlled trial with fourty-five professional soccer players aged 22.33 ± 4.82 years participated in the study. Twenty-three participants were assigned to the experimental group with peripheral electromagnetic stimulation (5 stimulations of 5 s at 100 HZ with 55 s of rest for a total of 5 min of treatment) and the remaining 22 participants were assigned to the control group. Pain pressure threshold (PPT) of the vastus medialis, the Visual Analogue Scale-Fatigue (VAS-F), half squat (HS) test and the maximum voluntary contraction of the quadriceps were assessed. All evaluations were performed before and after 1 h of the eccentric exercise induced DOMS, as well as at post 24–48, and 72 h.Results: Group-by-time interaction was observed in PPT of the vastus medialis (p = 0.040) with a medium effect size (η2p = 0.069). From 48 to 72 h the experimental group showed an increase of PPT compared to control group (p = 0.015). There was no group-by-time interaction for HS, quadriceps strength and VAS-F (p > 0.05).Discussion: Peripheral electromagnetic stimulation in male professional soccer players did not produce significant improvements in the power and strength of the lower limbs but decreased the peripheral sensitization of the vastus medialis after eccentric exercise protocol.Clinical Trial Registration:https://www.anzctr.org.au/Trial/Registration/TrialReview.aspx?id=384050&isReview=true, Identifier: ACTRN12622000841774.